Systematic Review of Research Trends in Environmental Literacy in Primary and Secondary Education: A Bibliometric Analysis 2016-2025 - Hanny Dwi Yonanda; Saiful Ridlo; Novi Ratna Dewi; Dyah Rini Indriyanti; Sri Ngabekti (Universitas Negeri Semarang, 2026)
The latest Programme for International Student Assessment assesses competencies in the context of environmental issues, making the strengthening of environmental education crucial for enhancing students' environmental literacy. This study aims to analyze the trends, implementation, and dominant topics of environmental literacy in primary to secondary education. A systematic literature review (SLR) was conducted following the PRISMA protocol. A primary data search was performed on the Scopus database using the keyword